O comérico justo na cadeia produtiva e os perfis de responsabilidade social - Gonçalves, Luiz Carlos (2007)
The principal objective of this dissertation was to evaluate the profiles of Social Responsibility of the great companies, through your purchase relationships with your suppliers of smaller load and samaller economical power. The importance of the study appears of the need of identifying if there are companies that use practices related to the Sustainable Development and the Social Responsibility in your purchase relationships; as well as verifying the existence of companies that they are used of Fair Trade's beginnings in your productive chains and which are the benefits of that approach. The study looks for to answer as the actions related to the Fair Trade they also benefit the society. The bibliography revision offered enough subsidies for the rising of secondary data, as well as for the accomplishment of the work through the method of study of only case, tends about unit of analysis a supplying company and your group of customers. The nature of the research is of descriptive and exploratory character. For the collection of the data the method of intensive direct documentation was used, with the application of internal interviews and of the method of extensive direct documentation, with the use of questionnaires distributed the customers, besides the analysis of the documents peculiar of the researched organization. Those information were analyzed with larger depth through the relationship of the evidences with the initial propositions of the study being used of a descriptive structure to organize the case study. The comparison among the data obtained in the interviews and in the questionnaires it demonstrated there to be correlation between the positioning of the supplying company and the one of the customers' group. In a general way, they were identified two profiles of companies buyers, with predominance of the group that bases your relationships on the liberal and neoliberal economic model, prioritizing your purchase strategy for the search of competitive advantages obtained by the reduction of the prices in your productive chain. The minority group already has as your characteristic principal the application of the precepts of the Sustainable Development, of the Social Responsibility and of the Fair Trade in the relationship with your suppliers and although it doesn't put aside obtaining your profits and of reducing your costs, it also worries about the social subjects and you adapt. It is ended that the largest adhesion on the part of the companies, society and governments to the practices that make possible the transition for the Sustainable Development, depends socially of the discovery of opportunities of businesses responsible transformed in profit with the consequent reduction of the marginal costs promoted by the liberal and neoliberal economic model, as well as that the Sustainable Development represents the incorporation of wide social aspirations, going from the real transformation of the production process, including changes in the patterns of capitalist development, as well as institutional modifications among the components of the market (stakeholders). However, it was verified private behaviors that impede the generalization of this result for all the cases, especially in the buyers' case to prefer smaller prices to the largest quality, only caring with the profit and not including in your concerns the social.